The System of Macroeconomic Accounts Statistics : An Overview. (Pamphlet Series; Pamphlet Series, ;, 2007)
Designed to meet the basic needs of economists and statisticians, this pamphlet is unique in providing an explanation of the key principles underlying macroeconomic statistics when viewed as an integrated system. It highlights the interrelationships between the various sectors and provides a bridge linking the various macroeconomic accounts statistics-national accounts, balance of payments, government finance statistics, and monetary and financial statistics-to assist the reader in understanding the main concepts underlying these statistics. It does so by simplifying many of the concepts, explaining common features and differences, showing how the four key statistical areas harmonize, and providing examples to demonstrate the practical application and uses of the concepts within the conceptual framework. The pamphlet completely updates Pamphlet No. 29, Macroeconomic Accounts: An Overview, by Poul Holst-Madsen, which was published in 1985.